(untitled) (Research, Society and Development, 2025)
Companies invest a large amount of money in sponsorship. The association between a sponsor and a sporting event is considered a very effective marketing strategy. One aspect that influences consumer response to sponsorship is the credibility of the sponsor. The purpose of this study was to examine the influence of sponsor credibility on consumer attitudes and intentions. Four hundred and seventy-four participants of two street race events were interviewed. Data were analyzed using the partial least squares structural equation modeling. The event organizer, a variable not fully explored in the literature, was also addressed. The perception of sponsor credibility had a positive influence on consumer attitudes toward the event organizer, the sponsor and the event. The sponsor’s credibility also positively affected the consumer’s intention to purchase the sponsor’s products and the word-of-mouth intention. These results confirm the importance of sponsor credibility in order to achieve favorable consumer behavior. The analysis of the role of the event organizer in the success of sponsorship introduces a new element to the study of sporting events.